Deciphering the regulatory landscape of fetal and adult gamma delta T-cell development at single-cell resolution - Sagar,; Pokrovskii, Maria; Herman, Josip S.; Naik, Shruti; Sock, Elisabeth; Zeis, Patrice; Lausch, Ute; Wegner, Michael; Tanriver, Yakup; Littman, Dan R.; Gruen, Dominic (EMBO Journal, 2020)
gamma delta T cells with distinct properties develop in the embryonic and adult thymus and have been identified as critical players in a broad range of infections, antitumor surveillance, autoimmune diseases, and tissue homeostasis. Despite their potential value for immunotherapy, differentiation of gamma delta T cells in the thymus is incompletely understood. Here, we establish a high-resolution map of gamma delta T-cell differentiation from the fetal and adult thymus using single-cellRNAsequencing. We reveal novel sub-types of immature and mature gamma delta T cells and identify an unpolarized thymic population which is expanded in the blood and lymph nodes. Our detailed comparative analysis reveals remarkable similarities between the gene networks active during fetal and adult gamma delta T-cell differentiation. By performing a combined single-cell analysis ofSox13, Maf,andRorcknockout mice, we demonstrate sequential activation of these factors duringIL-17-producing gamma delta T-cell (gamma delta T17) differentiation. These findings substantially expand our understanding of gamma delta T-cell ontogeny in fetal and adult life. Our experimental and computational strategy provides a blueprint for comparing immune cell differentiation across developmental stages.
CRIS-Team WoS Importer:2020-07-24